2017
DOI: 10.1007/s00068-017-0787-5
|View full text |Cite
|
Sign up to set email alerts
|

Violent trauma recidivism: Does all violence escalate?

Abstract: Recidivism for interpersonal violence results in a significant number of admissions to trauma centers. In our patient cohort, injury associated with successive blunt assaults did not worsen with subsequent admissions. Recidivism for gunshot wounds tends to be more severe and have a worse prognosis with each successive admission compared to outcomes associated with repeated stab wounds. Focused efforts should include rehabilitation efforts early in the post-injury period, especially in patients with a history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…As for predictors of reinjury, male sex was a significant risk factor for all forms of recidivism, consistent with literature on violent recidivism [ 11 , 21 , 22 ]. Furthermore, the 15–24-year-old patients in PRTH were found to be almost four times as likely to be recidivists.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As for predictors of reinjury, male sex was a significant risk factor for all forms of recidivism, consistent with literature on violent recidivism [ 11 , 21 , 22 ]. Furthermore, the 15–24-year-old patients in PRTH were found to be almost four times as likely to be recidivists.…”
Section: Discussionsupporting
confidence: 85%
“…A violent recidivism study by Kaufmann et al also conveyed this lack of value [ 21 ]. Yet, Nygaard et al stated a lower ISS was a predictor of violent recidivism [ 22 ]. The protective effect found in the severity markers could be due to consequential lifestyle or functional impairments which led to avoidance of the situation or environment, precautionary measures instilled, possible death due to trauma before a second admission, or loss of follow-up due to emigration.…”
Section: Discussionmentioning
confidence: 99%
“…The high proportion of these injuries being due to assault mean there is an increased risk of retaliation as well as a higher risk of a subsequent trauma, also known as injury recidivism [4, 10, 16]. A 2017 study of over 10,000 admissions in an urban level I trauma center found that of patients with a violent trauma (blunt assault, stabbing, or gunshot wound), patients admitted for a gunshot wound had a 13.5 times higher odds of mortality compared to blunt assault [17]. Compared to blunt assault and stabbings, patients who experienced gunshot wounds were the only violent injury in which severity of the injury increased with each additional hospital admission [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, as these findings also illustrate, while necessary, strains alone appear to be insufficient to fully explain the perpetration of violence and alternative or indeed complementary theories could help advance our understanding. For example, it has been speculated that the significant gender variations in violent offence is mediated by socially constructed, subjective gender norms (Blum et al, 2019; Nygaard et al, 2018; Topitzes et al, 2012; Zahn-Waxler et al, 2008). This study was unable to test for this; nevertheless, it was clear that the majority of this cohort was male and a significant proportion had histories of violent offending.…”
Section: Discussionmentioning
confidence: 99%